Alternative routes to intravenous tranexamic acid for postpartum hemorrhage: A systematic search and narrative review. (28th June 2022) - Shakur‐Still, Haleema; Grassin‐Delyle, Stanislas; Muhunthan, Kopalasuntharam; Ahmadzia, Homa K.; Faraoni, David; Arribas, Monica; Roberts, Ian
Abstract: Objective: To review available data on tranexamic acid (TXA) plasma concentration needed to inhibit fibrinolysis and the time to achieve this concentration when giving TXA by different routes in humans. To identify ongoing trials assessing alternatives to intravenous TXA administration. Methods: We updated two previous systematic reviews by searching MEDLINE, EMBASE, OviSP, and ISI Web of Science from database inception to July 2021. We also searched the WHO International Clinical Trials Registry Platform for ongoing trials to July 2021. Titles and abstracts were screened for relevant trials. Two reviewers independently reviewed and agreed the trials to be included. Results: Plasma TXA concentrations over 10 mg/L provide near maximal inhibition of fibrinolysis, with concentrations over 5 mg/L providing partial inhibition. Oral TXA tablets take about 1 h to reach a plasma concentration of 5 mg/L in postpartum women. Studies in healthy volunteers and shocked trauma patients show that intramuscular TXA achieves a plasma level of over 10 mg/L within 15 min. One trial is ongoing to determine the pharmacokinetics of intramuscular and oral solution TXA in pregnant women. Conclusion: Intramuscular TXA in healthy volunteers and shocked trauma patients reaches therapeutic concentration rapidly. Oral TXA tablets take too long to reach the minimum therapeutic concentration in postpartum women. Synopsis: Intravenous tranexamic acid (TXA) reduces death due to bleeding if given as soon as possible after birth and no later than 3 hours. TXA orally takes about 1 hour to reach minimum therapeutic concentration in postpartum women. Intramuscular TXA achieves therapeutic concentration within 5 minutes in healthy volunteers and in shocked trauma patients.